Exploring Canadian surgeons' decisions about postoperative weight bearing for their hip fracture patients. Issue 1 (6th October 2016) - Carlin, Leslie; Sibley, Kathryn; Jenkinson, Richard; Kontos, Pia; McGlasson, Rhona; Kreder, Hans J.; Jaglal, Susan
Abstract: For older adults with osteoporosis, a fall resulting in hip fracture is a life‐changing event from which only one‐third fully recover. Current best evidence argues strongly for elderly patients to bear weight on their repaired hip fracture immediately after their surgery to maximize their chances of full or nearly full recovery. Patient stakeholders in Canada have argued that some surgeons fail to issue "weight‐bearing‐as‐tolerated" (WBAT) orders in all eligible cases, protecting their bony repair but contributing to increased mortality and long‐term disability rates. In collaboration with a national stakeholder organization, Bone and Joint Canada, we interviewed 20 orthopedic surgeons across Canada who perform hip fracture repair surgery, with the aim of understanding their attitudes and behavior toward patient management regarding weight bearing. Qualitative content analysis, in which themes are identified and agreed by multiple coders, suggested that both patient characteristics and surgeon factors influence surgeons' postoperative weight‐bearing orders. While almost all respondents agreed that weight bearing as tolerated is indeed therapeutic for most hip fracture repair or replacement patients, surgeons also described certain patient characteristics that would diminish the value of immediate weight bearing, including poor bone quality and certain types of fracture pattern. Surgeon factors that affect postoperative mobilization orders include choice of construct, previous experience of construct failure, and lack of local audit data regarding past weight‐bearing decisions and patient outcomes. Thus, although familiar with best practice guidelines, surgeons also have "rules to break the rules." In an era when "good" medicine leans toward science rather than art, the role of individual experience in decision making with regard to hip fracture care continues to be important and would benefit from being discussed openly.